Direct determination of stresses from the stress equations of motion and wave propagation for a new class of elastic bodies. (January 2015) - Bustamante, R; Sfyris, D
For a new class of elastic bodies, where the linearized strain tensor is given as a function of the Cauchy stress tensor, the problem of considering unsteady motions is studied. A system of partial differential equations that only depends on the stress tensor is found from the equation of motion, which is a system of six partial differential equations for the six components of the stress tensor. A simple boundary value problem is solved for a 1D bar using exact and numerical methods.